Fluorescence and Turbidimetry Study of Complexation of Human Serum Albumin with Polycations - Güney, Orhan; Saraq, A. Sezai; Mustafaev, Mamed I. (SAGE Publications, 1997)
Complexation of poly(N-ethyl-4-vinylpyridinium bromide) (PEVP) and poly(N-ethyl/cethyl-4-vinylpyridinium bromide) (PECVP) with human serum albumin (HSA) was studied by fluorescence spectroscopy and turbidimetric titration in dilute aqueous solutions. Solubility of polycation-HSA complexes depends on the initial concentrations and ratios of the components, pH, hydrophobic-hydrophilic balance of the macromolecules, and existence of low molecular salt (NaCl). A soluble interpolymer complex which is formed at low concentrations of polycation is insoluble at high polycation concentrations. The average fluorescence quantum yield of HSA decreases as polycation binds to the protein. The maximum reduction in emission intensity of HSA indicates the number of the HSA molecules bound per polymer chain. Quenching of HSA fluorescence by PECVP is decreased in the presence of NaCl at pH 7.0 but not at pH 4.3.